(RE) CONSTRUCTING GENDER IN A NEW VOICE: THE ROLE OF GENDER IDENTITY IN SLA, THE CASE OF MALAYSIA - Cheng, Karen Kow Yip (k@ta: A Biannual Publication on the Study of Language and Literature, 2005)
This study is a qualitative study of Malaysian children aged between four and six years engaged in a story-telling task. The question posed in this piece of research then: Is the role played by gender in SLA? If it does play a role, what then is the nature of this role? The path taken by this study is to analyze discourse in story-telling.